2008
DOI: 10.1007/s10661-008-0392-5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variations of the quality of ambient air in the Kingdom of Bahrain during 2007

Abstract: The main objective of the present investigation is to study the temporal and spatial variations of the quality of ambient air in the Kingdom of Bahrain. The non-parametric Kruskal-Wallis (KW) test showed significant spatial variations and interactions of spatial-temporal among five mobile monitoring stations for 11 air pollutants. The Mann Whitney (MW) test demonstrated the seasonality of spring over winter for the PM(10), PM(2.5), NO(2), CO and p-xylene, the seasonality of winter over spring for O(3), and no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This raises the question as to whether ambient air pollution is one of the main contributing factors to the high number of under-five and maternal deaths in LMICs. Moreover, because of high spatial and temporal variations in the ambient air quality coupled with seasonal and time changes [12], more studies in different regions on the health effects of short-term and long-term exposure to different types of ambient PM 2.5 are necessary so as to effect policy changes on regional and/or global air quality standards. An investigation on the effect of ambient PM 2.5 on under-five and maternal mortality, as in this study, remains significant towards answering such questions and subsequently designing and implementing preventive measures that can lead to improved maternal, newborn, and child health (MNCH) in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…This raises the question as to whether ambient air pollution is one of the main contributing factors to the high number of under-five and maternal deaths in LMICs. Moreover, because of high spatial and temporal variations in the ambient air quality coupled with seasonal and time changes [12], more studies in different regions on the health effects of short-term and long-term exposure to different types of ambient PM 2.5 are necessary so as to effect policy changes on regional and/or global air quality standards. An investigation on the effect of ambient PM 2.5 on under-five and maternal mortality, as in this study, remains significant towards answering such questions and subsequently designing and implementing preventive measures that can lead to improved maternal, newborn, and child health (MNCH) in LMICs.…”
Section: Introductionmentioning
confidence: 99%
“…During any dust storm episode, 24-h mean PM 10 concentrations of over 1,000 mg/m 3 are recorded (Engelbrecht et al 2008(Engelbrecht et al , 2009, exceeding the World Health Organization (WHO) guidelines. According to the findings of Khamdan et al (2009), PM 10 and PM 2.5 originated from dust storms from the local desert and the trans-boundary airborne effects of the southern Iraqi desert impact Bahrain, Kuwait, and the eastern province of Saudi Arabia and perhaps extend further to the Arabian Gulf.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there existed significant difference for PM 10 , O 3-1hr , and SO 2 (values exceed the threshold) by testing location and season factors. However, Khamdan et al (2009) showed that there was a significant correlation between PM 10 levels that exceeded the threshold and haze episodes, but that there were not significant differences with location and seasons. In roadside sites, the appearance of severe episodic air pollution events from PM 10 , CO 8hr , NO 2 , and SO 2 were associated with calm conditions (WS = 1.19 m/s), when air mass stagnation is favoured.…”
Section: Air Quality and Standardsmentioning
confidence: 83%